2023
DOI: 10.1007/s10147-023-02414-x
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical and imaging features of interstitial lung disease in cancer patients treated with trastuzumab deruxtecan

Tomohisa Baba,
Masahiko Kusumoto,
Terufumi Kato
et al.

Abstract: Background Interstitial lung disease/pneumonitis (ILD/pneumonitis) has been identified as a drug-related adverse event of special interest of trastuzumab deruxtecan (T-DXd), but there were a few reports of T-DXd-related ILD/pneumonitis in clinical practice. Methods Between May 25, 2020 (the launch of T-DXd in Japan) and February 24, 2022, there were 287 physician-reported potential ILD/pneumonitis cases from the Japanese post-marketing all-case surveillanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…These findings are similar to previous reports of higher risk of ILD or pneumonitis with T-DXd treatment in Japanese patients [24], and may be linked to underlying biologic factors or Japanese-specific management/monitoring practices. Further, a real-world study of T-DXd use in Japan since its launch in 2020 reported that the most common ILD radiologic patterns were organizing pneumonia, hypersensitivity pneumonitis, and diffuse alveolar damage (DAD), with the DAD subtype being associated with poor prognosis [25]. Based on experience of gefitinibinduced ILD [26], healthcare providers in Japan have a high awareness of ILD and more experience in proactively detecting ILD, even at grade 1 stage (i.e., ILD manifesting only as abnormal high-resolution computed tomography) and intensively managing ILD.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are similar to previous reports of higher risk of ILD or pneumonitis with T-DXd treatment in Japanese patients [24], and may be linked to underlying biologic factors or Japanese-specific management/monitoring practices. Further, a real-world study of T-DXd use in Japan since its launch in 2020 reported that the most common ILD radiologic patterns were organizing pneumonia, hypersensitivity pneumonitis, and diffuse alveolar damage (DAD), with the DAD subtype being associated with poor prognosis [25]. Based on experience of gefitinibinduced ILD [26], healthcare providers in Japan have a high awareness of ILD and more experience in proactively detecting ILD, even at grade 1 stage (i.e., ILD manifesting only as abnormal high-resolution computed tomography) and intensively managing ILD.…”
Section: Discussionmentioning
confidence: 99%